Analisis Rasio Likuiditas Dan Rasio Profitabilitas Terhadap Pengukuran Kinerja Keuangan Pada PT Unilever Indonesia Tbk Periode Tahun 2013-2023 - Gea Annastasya; Eka Rahim (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research aims to determine and analyze the financial performance of PT Unilever Indonesia Tbk using liquidity ratios, profitability ratios and market ratios. The analytical method used in this research is associative analysis. The data source for this research is documentation in the form of the annual financial report of PT Unilever Indonesia Tbk from 2013 to 2023. This research uses an associative approach. Based on the results of the analysis and discussion, the financial performance of PT Unilever Indonesia Tbk is measured using the liquidity ratio in the Current Ratio, which is an average of 64.90%, which is not good because it is below the industry standard of 200% and the Quick Ratio is an average of 64.90%. 43.32% is in bad condition because it is below the industry standard of 150%. The profitability ratio on Net Profit Margin is an average of 16.23% which is in poor condition because it is below the industry standard of 20%, Return On Assets is an average of 36.21% which is in good condition and is above the industry standard of 30% and an average Return On Equity of 132.52% in good condition and above the industry standard of 40%. Meanwhile, the market ratio on Price to Book Value on average is 19.32, which is overvalued because it is very high compared to the general industry standard of 1.